The Problem of Hell. - Kvanvig, Jonathan L. (Oxford University Press, 1994)
This treatise argues that the traditional Christian understanding of hell fails to solve the problem of hell from a philosopher's viewpoint, as it has been constructed from a retributive model. The author develops a philosophical account of hell which does not depend on the retributive model.